2018
DOI: 10.1002/wrna.1469
|View full text |Cite
|
Sign up to set email alerts
|

Complex HuR function in pancreatic cancer cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal cancers with dismal patient outcomes. The underlying core genetic drivers of disease have been identified in human tumor specimens and described in genetically engineered mouse models. These genetic drivers of PDAC include KRAS signaling, TP53 mutations, and genetic loss of the SMAD4 tumor suppressor protein. Beyond the known mutational landscape of PDAC genomes, alternative disrupted targets that extend beyond conventional genetic mutations hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 93 publications
0
28
0
Order By: Relevance
“…Previous studies showed that HuR promotes proliferation in cancer cells (20,38), including wild-type gliomas (39,40). Here, we investigated the effect of HuR expression on cell proliferation in cancer cells that harbor a natural heterozygous IDH1 mutation.…”
Section: Hur Promotes Cell Proliferation and Invasion In Mutidh1 Canmentioning
confidence: 98%
“…Previous studies showed that HuR promotes proliferation in cancer cells (20,38), including wild-type gliomas (39,40). Here, we investigated the effect of HuR expression on cell proliferation in cancer cells that harbor a natural heterozygous IDH1 mutation.…”
Section: Hur Promotes Cell Proliferation and Invasion In Mutidh1 Canmentioning
confidence: 98%
“…There are a number of reports, which link pro-tumor activity of HuR/ELAVL1 with cancer of different localizations [64][65][66][67][68]. Surprisingly, HuR/ELAVL1 binding to different long non-coding RNAs induces opposite effect on the proliferation of different tumor cells [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…HuR, a member of ELA V family of RBPs ,High HuR protein expression is found in both the nucleus and cytoplasm of human colorectal cancer [14]. HuR protein can recognize and combined messenger RNA of target genes, thus stable target genes to inhibit the degradation of messenger RNA, participate in the post-transcriptional regulation of target genes, and regulate a variety of physiological and biochemical processes such as tumor cell growth, proliferation, differentiation, signal transduction, transcription and translation, angiogenesis, protein transport, cell apoptosis and its metabolism [31]. The insulin-like growth factor-2 mRNA binding proteins (IGF2BPs or IMPs) belong to a conserved subfamily of RBPs.…”
Section: Discussionmentioning
confidence: 99%